Penerapan Desain Arsitektur Metafora Pada Perancangan Gedung Orkestra di Kota Yogyakarta - Tio Setyawan; Anggraeni Dyah Sulistiowati; Harfa Iskandaria (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2020)
The orchestra building is a place or building that accommodates and serves privately owned music concert activities that have facilities for teaching and learning activities regarding orchestral music and its supporting facilities, by applying an idea or a metaphorical architectural design that is embodied in the form of a building. Metaphorical architecture in the application of the orchestra building metaphorizes from a musical instrument. The shape of the building which is the result of the metaphor of a violin instrument, so that it can create a different impression from each visitor who uses the building and is able to produce expressive building forms.